The Effect of Employee Happiness on Employee Performance in UAE: The Moderating Role of Spirituality and Emotional Wellness - Awada, Nesreen; Sarawati Hj. Johar, Siti; Binti Ismail, Fadillah (International Journal of Psychosocial Rehabilitation, 2020)
Happiness is the ultimate goal of life. There are few studies that examined the effect of employee happiness on employee performance, and most of these studies examined employee happiness in the context of business organizations in developed countries. In addition, few studies examined the employee's spiritual and emotional wellness. The purpose of this study is to examine the effect of employee happiness on employee spiritual and emotional wellness and employee performance in the public sector of the United Arab Emirates (UAE). The study also aims to examine the moderating role of employee spiritual and emotional wellness. The population of this study is the public servants in Abu Dhabi and Dubai. A random sampling technique is deployed. The instrument of data collection is a questionnaire. The questionnaire was validated, and a pilot study was conducted prior to data collection. Data examination was conducted using the Statistical Package for Social Science (SPSS). The hypotheses of this study were tested using Smart Partial Least Square (Smart PLS). The findings indicated that employee happiness has a significant effect on employee performance and spiritual and emotional wellness. Employee spiritual and emotional wellness moderated the effect of employee happiness on employee performance. Decision makers are recommended to increase the employee happiness, spirituality, and emotional wellness at the workplace.